2014
DOI: 10.1105/tpc.114.125849
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Pore Residue Renders the Arabidopsis Root Anion Channel SLAH2 Highly Nitrate Selective

Abstract: In contrast to animal cells, plants use nitrate as a major source of nitrogen. Following the uptake of nitrate, this major macronutrient is fed into the vasculature for long-distance transport. The Arabidopsis thaliana shoot expresses the anion channel SLOW ANION CHANNEL1 (SLAC1) and its homolog SLAC1 HOMOLOGOUS3 (SLAH3), which prefer nitrate as substrate but cannot exclude chloride ions. By contrast, we identified SLAH2 as a nitrate-specific channel that is impermeable for chloride. To understand the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 53 publications
3
74
0
1
Order By: Relevance
“…A recent study showed that SLAH2 was able to specifically interact with and be activated by CPK21 and CIPK23 (Maierhofer et al, 2014). Therefore, SLAH2 could be activated and regulated by multiple CPKs in roots, similar to the activation of SLAC1 and SLAH3 by multiple CPKs in guard cells.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…A recent study showed that SLAH2 was able to specifically interact with and be activated by CPK21 and CIPK23 (Maierhofer et al, 2014). Therefore, SLAH2 could be activated and regulated by multiple CPKs in roots, similar to the activation of SLAC1 and SLAH3 by multiple CPKs in guard cells.…”
mentioning
confidence: 92%
“…We then constructed constitutively active versions of these kinases. According to previous reports, the deletion of the EF hands of CPKs renders the kinases Ca 2+ -insensitive and thus leads to a constitutively active form of the CPKs (Geiger et al, 2010(Geiger et al, , 2011Scherzer et al, 2012;Maierhofer et al, 2014). We then generated the truncated versions of the CPK2, CPK4, and CPK11 by deleting their EF hand domains and named these truncated CPKs CPK2ΔEF, CPK4ΔEF, and CPK11ΔEF, respectively.…”
Section: Activation Of Slah2 By the Constitutively Active Version Ofmentioning
confidence: 99%
See 3 more Smart Citations